Domino Dumping, I: Competitive Exporters - Anderson, James E. (American Economic Review, 1992)
When exporting firms face the prospect of voluntary export restraints (VER's), they have an incentive to export more than with no prospect of a VER, since greater exports lead to larger license allocations in the event of a VER. Export-country governments' incentives differ, leading either to export tax or subsidy, depending on the circumstances. The prospect of one departure from free trade thus leads to another, a domino effect. Anti-dumping enforcement will ordinarily not eliminate and ironically may increase dumping, toppling another domino.